A longitudinal, narrative study of professional socialisation among health students. Issue 4 (7th January 2021) - Price, Sheri L.; Sim, Sarah Meaghan; Little, Victoria; Almost, Joan; Andrews, Cynthia; Davies, Harriet; Harman, Katherine; Khalili, Hossein; Sutton, Evelyn; LeBrun, Jeffery
Abstract: Purpose: Interprofessional collaboration (IPC) among health professionals is well‐recognised to enhance care delivery and patient outcomes. Emerging evidence suggests that the early socialisation of students in health professional programmes to teamwork may have a positive impact on their future as collaborative practitioners. With a purpose of contributing to growing evidence on the processes of professional identity construction, and to explore how early expectations and perceptions of IPC develop during professional socialisation and pre‐licensure education, our study examined the early professional socialisation experiences among five groups of health professional students. Method: A qualitative, narrative approach was used to examine early professional socialisation among five programmes of health professional students (dentistry, medicine, nursing, pharmacy, physiotherapy) at an Atlantic Canadian University. In March and October 2016, students participated in interviews after first term (n = 44) and first year of study (n = 39). Interviews focused on participants' professional identify formation, as well as their perceptions and experiences of IPC. The authors analysed interview transcripts using narrative analysis. Results: Findings identify that despite the espoused importance of IPC within health professional training, students have a limited understanding of their professional roles and are largely focused on developing a uniprofessional, vs. interprofessional identity. Clinical experiences, role models and exposure to teamwork are critical to contextualise collaborative practice and enhance the development of an interprofessional identity. Conclusions: Findings can be used to guide the development of curricula that promote interprofessional identity development and IPC during early professional socialisation. Abstract : Despite the espoused importance of interprofessional education, professional socialization enabling interprofessional identity formation and promoting collaboration requires curriculum development and strategic recruitment.